2021
DOI: 10.1111/jcmm.16447
|View full text |Cite
|
Sign up to set email alerts
|

PP1, PKA and DARPP‐32 in breast cancer: A retrospective assessment of protein and mRNA expression

Abstract: Cyclic AMP-dependent protein kinase A (PKA) and protein phosphatase 1 (PP1) are multifunctional proteins involved in numerous essential signalling pathways that modulate physiological and pathological functions which have been implicated in cancer development and progression. Both PKA and PP1 are oligomeric enzymes composed of catalytic and regulatory subunits. PKA is a heterotetramer of two catalytic (encoded by PRKACA, PRKACB, PRKACG) and two regulatory (encoded by PRKAR1A, PRKAR1B, PRKAR2A, PRKAR2B) subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…RPS21 ’s role in breast cancer is not clear now, but one transcript of RPS, AA-RPS21 , is differentially expressed in cancerous tissues, indicating its potential driver role in breast cancer [34]. PPP1CA together with PRKACG and PRKAR1B were found to be the most strongly associated with breast cancer–specific survival [35]. Study found that inhibition of TXNIP via Myc drove Triple-negative breast cancers aggressiveness and was associated with decreased metastasis-free survival and decreased overall survival in breast cancer [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RPS21 ’s role in breast cancer is not clear now, but one transcript of RPS, AA-RPS21 , is differentially expressed in cancerous tissues, indicating its potential driver role in breast cancer [34]. PPP1CA together with PRKACG and PRKAR1B were found to be the most strongly associated with breast cancer–specific survival [35]. Study found that inhibition of TXNIP via Myc drove Triple-negative breast cancers aggressiveness and was associated with decreased metastasis-free survival and decreased overall survival in breast cancer [36].…”
Section: Resultsmentioning
confidence: 99%
“…PPP1CA together with PRKACG and PRKAR1B were found to be the most strongly associated with breast cancer-specific survival [35]. Study found that inhibition of TXNIP via Myc drove Triple-negative breast cancers aggressiveness and was associated with decreased metastasis-free survival and decreased overall survival in breast cancer [36].…”
Section: Human Breast Cancer Data (Bc23209_c1_stdata)mentioning
confidence: 93%
“…Recently, it was shown that breast cancer patients with elevated DARPP-32 expression but low PP1 expression have worse overall survival than those with low expression of DARPP-32 52 , suggesting a strong inverse correlation between PP1 and DARPP-32 proteins in patient outcome. This supports the notion that DARPP-32–mediated inactivation of PP1 functions via phosphorylation leads to increased activation of kinases involved in oncogenic signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the previous finding showing DARPP-32 is phosphorylated by PKA, Hansen and colleagues showed that Wnt-5A-mediated phosphorylation of DARPP-32 Thr-34 reduces breast cancer cell migration, and DARPP-32 phosphorylation is tightly regulated by intracellular cAMP levels and subsequent PKA activation 39 . Recently, it was shown that breast cancer patients with elevated DARPP-32 expression but low PP1 expression have worse overall survival than those with low expression of DARPP-32 52 , suggesting a strong inverse correlation between PP1 and DARPP-32 proteins in patient outcome. This supports the notion that DARPP-32-mediated inactivation of PP1 functions via phosphorylation leads to increased activation of kinases involved in oncogenic signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the notion that DARPP-32-mediated inactivation of PP1 functions via phosphorylation leads to increased activation of kinases involved in oncogenic signaling pathways. Moreover, PKA protein expression in breast tumor tissues shows a strong correlation with DARPP-32 and PP1 protein expression, warranting further investigation to understand their molecular role in regulating breast tumorigenesis 52 . In a separate study, Hansen et al reported that PKA protein activated by Wnt-5a ligands regulates breast cancer cell migration by phosphorylating DARPP-32 at Thr-34 in a PP1/CREB-dependent manner 39 .…”
Section: Discussionmentioning
confidence: 99%